Energy-saving retrofitting of traditional dwellings in the Hehuang region via multiobjective optimization - Zhao, Wenyu; Wu, Zhongtie; Zhao, Peizuo; Li, Leilei (Frontiers in Physics, 2025)
IntroductionEnergy consumption and indoor thermal comfort are critical issues in building design, especially in regions with harsh climates. In rural areas, traditional dwellings face challenges in managing heating demands and maintaining comfort during winter. This study proposes a multi-objective optimization strategy to improve energy efficiency and thermal comfort in these buildings.MethodsUsing the Non-dominated Sorting Genetic Algorithm II (NSGA-II) and EnergyPlus simulations, the study optimizes key design parameters such as roof insulation, wall insulation, and window thermal transmittance.ResultsThe findings highlight the importance of selecting appropriate insulation materials and their optimal thicknesses to balance energy savings and comfort. The results provide practical insights for energy-saving retrofits in cold, dry climates, offering a cost-effective and scientifically validated approach for enhancing building performance.DiscussionAs rural communities, including those in the Hehuang region, face increasing natural disasters, this research provides timely guidance for building designs that improve resilience and sustainability.